Application of Mycorrhizal Inoculum and Moringa Leaf Extract to Improve Growth and Yield of Soybean (Glycine max L.) on Alluvial Soil - Agnes Tutik Purwani Irianti; Agus Suyanto; Sherly Oktarianti; Edi Kurniadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Soybean (Glycine max L.) production in Indonesia faces persistent challenges, with productivity declining from 16.70 quintals/ha in 2021 to 14.56 quintals/ha in 2023. Alluvial soils in West Kalimantan, encompassing approximately 1,495,033 ha, present opportunities for soybean expansion but are constrained by low pH, poor nutrient availability, and suboptimal biological activity. This study investigated the combined effects of arbuscular mycorrhizal fungi (AMF) inoculation and moringa (Moringa oleifera) leaf extract application on soybean growth and productivity on alluvial soil. A factorial completely randomized design was employed with AMF doses (0, 5, and 10 g/polybag) and moringa leaf extract volumes (150, 200, and 250 ml polybag⁻¹ at 20% v/v), replicated three times. Two-way factorial ANOVA showed significant main effects and significant interaction effects (M×E) between AMF and moringa extract for all measured variables (P < 0.05 or P < 0.01). The combination of AMF at 10 g/polybag with moringa extract at 250 ml/polybag (M₂E₃) produced optimal results with 97.2 pods/plant and 48.6 g seed dry weight (DW) per plant, representing increases of 129% and 191% over the non-mycorrhizal lowest-dose control (M₀E₁), respectively. These findings suggest that integrated application of AMF and moringa extract represents a promising strategy for improving soybean productivity on marginal alluvial soils, pending field-scale validation.